The Capture of the Domestic Market by Russian Merchants in XVI-XVII Centuries - Mikhail Mikhailovich Shumilov (Управленческое консультирование, 2018)
The article considers an important aspect of the economic history of pre-Petrine Russia. The author analyzes government policies which aim to restrict economic activity of foreign merchants in the domestic Russian market. The main attention is focused on the clarifying the causes, the results and the peculiarities of trade protectionism policy pursued in the interests of the Treasury and the upper Russian merchants.